Structural and physicochemical characteristics of lintnerized native and sour cassava starches - Franco, Célia M. L. [UNESP]; Cabral, Renato A. F. [UNESP]; Tavares, Débora Q. (My University, 2002)
The comprehension of the structure of starch granules is important for the understanding of its physicochemical properties. Native and sour cassava starches after being analyzed with respect to their pasting properties and baking expansion capacity, were treated with 2.2 N HCl at 38 °C for a maximum of nine days. The starch granules remaining after lintnerization were analyzed for amylose content and intrinsic viscosity, by X-ray diffraction, scanning electron microscopy and chromatographic analysis. The results indicated that the acid hydrolysis on all starches occurred in two steps. The first one, with high hydrolysis rate, was characterized by a quick degradation of the amorphous part of the granules whereas the second step, with lower hydrolysis rate, was characterized by a higher resistance of the organized areas of the granules to acid treatment. Most of the amylose chains were found in the amorphous areas of starch granules only a small percentage was involved in the crystalline regions. The microscopic and chromatographic analysis demonstrated that the acid hydrolysis was not able to disrupt the entire granular crystalline structure. Fermented starch showed amylose and/or amylopectin chain fractions resistant to pullulanase, probably due to structural alterations during fermentation.
Keywords: Lintnerization; Physicochemical characteristics; Starch structure